Occurrence of Typhoid Fever Complications and Their Relation to Duration of Illness Preceding Hospitalization: A Systematic Literature Review and Meta-analysis. (30th October 2019) - Cruz Espinoza, Ligia María; McCreedy, Ellen; Holm, Marianne; Im, Justin; Mogeni, Ondari D; Parajulee, Prerana; Panzner, Ursula; Park, Se Eun; Toy, Trevor; Haselbeck, Andrea; Seo, Hye Jin; Jeon, Hyon Jin; et al.
Abstract: Background: Complications from typhoid fever disease have been estimated to occur in 10%–15% of hospitalized patients, with evidence of a higher risk in children and when delaying the implementation of effective antimicrobial treatment. We estimated the prevalence of complications in hospitalized patients with culture-confirmed typhoid fever and the effects of delaying the implementation of effective antimicrobial treatment and age on the prevalence and risk of complications. Methods: A systematic review and meta-analysis were performed using studies in the PubMed database. We rated risk of bias and conducted random-effects meta-analyses. Days of disease at hospitalization (DDA) was used as a surrogate for delaying the implementation of effective antimicrobial treatment. Analyses were stratified by DDA (DDA <10 versus ≥10 mean/median days of disease) and by age (children versus adults). Differences in risk were assessed using odds ratios (ORs) and 95% confidence intervals (CIs). Heterogeneity and publication bias were evaluated with the I 2 value and funnel plot analysis, respectively. Results: The pooled prevalence of complications estimated among hospitalized typhoid fever patients was 27% (95% CI, 21%–32%; I 2 = 90.9%, P < .0001). Patients with a DDA ≥ 10 days presented higher prevalence (36% [95% CI, 29%–43%]) and three times greater risk of severe disease (OR, 3.00 [95% CI, 2.14–4.17]; P < .0001) than patients arriving earlier (16% [95% CI, 13%– 18%]). Difference in prevalence and risk by age groups were not significant. Conclusions: This meta-analysis identified a higher overall prevalence of complications than previously reported and a strong association between duration of symptoms prior to hospitalization and risk of serious complications.